2004
DOI: 10.1159/000077971
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Uterine Artery Flow Velocity Waveforms at 12–14 and 22–24 Weeks of Gestation in Relation to Pregnancy Outcome and Birth Weight

Abstract: Objective: Uterine artery flow velocity was prospectively assessed using Doppler ultrasound at 12–14 and 22–24 weeks of gestation in the prediction of subsequent complications related to uteroplacental insufficiency: preeclampsia, pregnancy-induced hypertension, fetal growth restriction, fetal death and placental abruption, and to elucidate its relationship with birth weight. Methods: Uterine artery Doppler assessment was obtained during routine ultrasound screening in 263 unselected women. Flow velocity wavef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 16 publications
2
30
0
7
Order By: Relevance
“…In addition, both resistance indices decreased. Research using Doppler technology to assess changes during pregnancy in women suggests that to have better placentation and a greater birth weight, uterine artery resistance needs to decrease early for better fetal and maternal health [22,23]. For example, in human pregnancies, when uterine artery resistance remains high or does not decrease during the last third of gestation, there is an association with deficiency in nutrient supply.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both resistance indices decreased. Research using Doppler technology to assess changes during pregnancy in women suggests that to have better placentation and a greater birth weight, uterine artery resistance needs to decrease early for better fetal and maternal health [22,23]. For example, in human pregnancies, when uterine artery resistance remains high or does not decrease during the last third of gestation, there is an association with deficiency in nutrient supply.…”
Section: Discussionmentioning
confidence: 99%
“…7 Thus, the baseline risk of preeclampsia or intrauterine growth retardation should be estimated and low-dose aspirin started early on the presence of significant historic risk factors, such as previous severe preeclampsia or moderate to severe renal insufficiency. 8 A 2-stage Doppler artery screening in first and second trimester could also define a high-risk population, 9 and promising results have been published for aspirin prevention with first-trimester uterine artery Doppler selection in high-risk pregnancies. Response:…”
mentioning
confidence: 99%
“…Martinez et al, Carbillon et al, Melchiorre K et al found that compared with the normal pregnancies, complicated pregnancies had significantly higher persistence of a bilateral notch. 22,23 The presence of bilateral notches in the first-trimester uterine artery waveform was a relatively poor predictor of pre-eclampsia because of the high prevalence of this finding in normal pregnancies concluding that early bilateral notching alone is unlikely to be useful in screening for pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%